PROFIL FISIKA DAN KIMIA MINYAK ATSIRI DARI JENIS TUMBUHAN LITSEA DENGAN METODE PENYULINGAN PEREBUSAN - Agmi Sinta Putri; Risniyanti Manurung; Enih Rosamah; Harlinda Kuspradini (Tengkawang : Jurnal Ilmu Kehutanan, 2023)
English translation. The genus Litsea is a type of essential oil-producing plant found in the Educational Forest Laboratory of the Faculty of Forestry, Mulawarman University, Samarinda. The aim of this work is to examine the physical profile and identified the essential oil components from three types of Litsea (Litsea angulata, L. rubiginosa and L. elliptica). Distillation process of essential oils using a boiled system (water distillation). The physical characteristics of essential oils tested include yield, visual color and refractive index measured by a hand refractometer, as well as chemical profile such as essential oil components through GC-MS analysis. L. angulata obtained the higest rendemen was 0.13%. The essential oils of L. angulata, L. elliptica, and L. rubiginosa gained various colors, that were clear, yellowish, and dark yellow (respectivelly). L. rubiginosa oil has the greatest refractive index value about 1.442. The results of constituent identification by GCMS showed L. angulata oil composed by the main compounds were Cyclohexanemethanol (25.96%); 2-Undecanol (25.54 %); and 7-Octen-ol (14.09 %). The major constituent contained in the L. rubiginosa oils are Tetratetracontane (22.52 %); Spathulenol (10.39 %); and Heptacosane (9.88 %). L. elliptica is dominated by 7- Octen-2ol.2.6-Dimethyl (32.24 %); 2-Undecanol (30.31 %); and 9-Decen-2-ol (17.86%) as the main components. Analysis of chemical compounds with GC-MS showed that these three types of essential oils from Litsea plants are dominated by the monoterpene, alcohol, sesquiterpene, and others group.Keywords: Essential oil, GC-MS, Litsea angulata, Litsea elliptica, Litsea rubiginosa. AbstrakGenus Litsea merupakan jenis tumbuhan penghasil minyak atsiri yang ditemukan di Laboratorium Hutan Pendidikan Fakultas Kehutanan Universitas Mulawarman Samarinda. Tujuan dari riset ini untuk menganalisis sifat fisik dan mengidentifikasi komponen penyusun minyak atsiri dari tiga jenis Litsea (Litsea angulata, L. rubiginosa dan L. elliptica). Proses penyulingan minyak atsiri menggunakan metode rebus (water distillation). Sifat fisik minyak atsiri yang diujikan meliputi rendemen, warna, dan nilai indeks bias yang diukur menggunakan hand refractometer, serta sifat kimia berupa komponen kimia melalui analisis GC-MS. L. angulata memperoleh rendemen tertinggi sebesar 0,13%. Minyak L. angulata, L. elliptica, dan L. rubiginosa menghasilkan warna yang beragam yaitu bening, kekuningan, dan kuning pekat (berturut-turut). Minyak L. rubiginosa mempunyai nilai indeks bias tertinggi yaitu 1,442. Hasil identifikasi senyawa dengan GC-MS menunjukkan minyak L. angulata tersusun atas komponen utama Cyclohexanemethanol (25,96%); 2-Undecanol (25,54 %); dan 7-Octen-ol (14,09 %). Komposisi utama yang terkandung pada minyak L. rubiginosa diantaranya Tetratetracontane (22,52 %); Spathulenol (10,39 %); dan Heptacosane (9,88 %). Minyak L. elliptica didominasi oleh 7- Octen-2ol.2.6-Dimethyl (32,24 %); 2-Undecanol (30,31 %), dan 9-Decen-2-ol (17,86%) sebagai penyusun utama. Analisis komponen kimia menunjukkan bahwa ketiga jenis minyak atsiri tumbuhan genus Litsea ini didominasi dengan kelompok monoterpene, alkohol, seskuiterpen, dan kelompok senyawa lain-lain.Kata kunci: Minyak Atsiri, GC-MS, Litsea angulata, Litsea elliptica, Litsea rubiginosa.